2008
DOI: 10.1007/bf03246484
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthesis for new substituted imidazoles

Abstract: This paper is dedicated to Professor Habib Firouzabadi on the occasion of his honourable retirement and for his continous, past and future devotions and endeavours to the field of organic chemistry.MMH owes him a personal debt of deep gartitude for his encourgments and friendships.The addition of dimethyl acethylendicarboxylate (DMAD) to thiosemicarbazone and guanylhydrazone of aldehydes afforded compoundes which were characterized to be new substituted imidazoles. Their structures were determined by 'n NMR, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has been reported that, thioxoimidazole derivatives were isolated from the reaction of arylthiosemicarbazones with dimethyl acetylenedicarboxylate (DMAD) . Also, Vijesh et al suggested that imidazolethione derivatives containing substituted pyrazole moiety were obtained upon treatment of substituted thiosemi‐carbazones containing pyrazole ring with DMAD .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that, thioxoimidazole derivatives were isolated from the reaction of arylthiosemicarbazones with dimethyl acetylenedicarboxylate (DMAD) . Also, Vijesh et al suggested that imidazolethione derivatives containing substituted pyrazole moiety were obtained upon treatment of substituted thiosemi‐carbazones containing pyrazole ring with DMAD .…”
Section: Introductionmentioning
confidence: 99%